he Variation Effect of Doping Percentage upon Radiative FluorescenceTransitions for Nd: glass - Haider, Adawiya J; Al-Zubaidi, Shehab A; Ahmed, Duha S; Majeed, Lina Y (Al-Nahrain Journal of Science, 2018)
In this work we determine an optimum set of intensity parameters ( ) ( ) W t by using the standard least-square fitting. The values of radiative transition probability ( Arad ), radiative lifetime ( c rad t ) and emission branching ratio coefficient ( br ) have been determined for the major excited state .The present work focuses on the absorption bands at 530.81 nm wavelength for the active medium, which coincidences with the emission spectrum of the diode laser which is commonly used to pump the solid state laser.